Effect of Acupotomy Intervention on Fibrosis of Rectus Femoris in Rabbits with Knee Osteoarthritis - LIU Jing; ZENG Weiquan; LIN Qiaoxuan; LU Liming; GUO Zexing; LIU Hong; ZHANG Liangzhi; XIU Zhongbiao (康复学报, 2021)
Objective: To observe the effects of acupotomy intervention on the fibrosis of the rectus femoris in rabbits with knee osteoarthritis from the histological and molecular level, and to reveal the possible mechanism of the needle knife in the treatment of knee osteoarthritis.MethodsTwenty-four healthy male New Zealand rabbits were randomly divided into blank group, model group and acupotomy group used by random number table method, with 8 rabbits in each group. Modified Videman method was used to replicate the osteoarthritis model of the knee with left hind limb extended plaster immobility for 6 weeks. Lequesne MG knee joint grade score, X-ray and MRI imaging examination of knee joint and pathological morphology of rectus femoris were confirmed after successful modeling. In acupotomy group, the transfascial focal points of quadriceps femoris muscle were released by acupotomy under the guidance of Jingjin theory, treatment points included "Hedingci" (the focal lesion point of the foot yangming meridian, located at the attachment of the positive upper margin of the quadriceps tendon and the patella), "Binwaishang" (the focal lesion point of the foot yangming meridian, located at the attachment of the lateral upper edge of the patella to the lateral femoral muscle tendon), "Binneishang" (the focal lesion point of the foot yangming meridian, located at the attachment of the medial femoral muscle tendon to the inner upper edge of the patella), once a week, for a total of 4 times of treatment. The blank group and model group were routinely fed and grabbed without intervention. One week after the end of intervention, masson staining was used to detect the changes in the tissue morphology and collagen volume fraction of the rectus femoris to observe the effect of acupotomy on the fibrosis of the rectus femoris in rabbits with knee osteoarthritis. RT-PCR and Western blot were used to detect the mRNA and protein expression levels of type Ⅰ collagen fibers (ColⅠ), vimentin (VIM), and Alpha-smooth muscle actin (α-SMA) in the rectus femoris muscle to observe the effect of acupotomy on the knee osteoarthritis.Results1) Masson staining results showed that neat red-stained skeletal muscle fibers can be seen in the blank group; skeletal muscle fibers can be seen in the model group damaged and surrounded by a large amount of blue-stained collagen fibers; in the acupotomy group, skeletal muscle fibers can be seen neatly and a small amount of blue-stained collagen fibers wrap around. Compared with the blank group, the collagen volume fraction of rectus femoris muscle in the model group increased, and the difference was statistically significant (P<0.01). Compared with the model group, the acupotomy group had decreased collagen volume fraction of rectus femoris muscle, and the difference was statistically significant (P<0.01). 2) RT-PCR results showed that the mRNA expressions of ColⅠ, VIM and α-SMA in the model group were significantly higher than those in the blank group (P<0.01), while those in the acupotomy group were significantly lower than those in the model group, and the difference was statistically significant (P<0.01). 3) Western blot results showed that the proteins expressions of ColⅠ, VIM and α-SMA in the model group were significantly higher than those in the blank group (P<0.01), while those in the acupotomy group were significantly lower than those in the model group, and the difference was statistically significant (P<0.01).ConclusionBased on the Jingjin theory, the release of quadriceps femoris' transfascial focal point by acupotomy can down-regulate the expression levels of mRNA and protein of ColⅠ, VIM, α-SMA, and reduce the degree on fibrosis of rectus femoris muscle, which may be one of the mechanisms of acupotomy for KOA.